Intelligent planning and simulation of 5G wireless network - Jun LI (Dianxin kexue)
Traditional planning methods based on human experience have been limited for 5G networks.It is urgent to introduce intelligent planning methods for 5G wireless networks based on large data analysis.Athree-step closed-loop planning scheme of 5G intelligent station location planning,parameter planning and post-evaluation was proposed.A 5G wireless network intelligent planning system was built and applied to the actual 5G wireless network planning and simulation,which effectively supports the future 5G wireless networking deployment,ensures the precise investment of resources,and lays the foundation for the construction of 5G high-quality target network.